2016
DOI: 10.1016/j.stemcr.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Lack of T Cell Response to iPSC-Derived Retinal Pigment Epithelial Cells from HLA Homozygous Donors

Abstract: SummaryAllografts of retinal pigment epithelial (RPE) cells have been considered for the treatment of ocular diseases. We recently started the transplantation of induced pluripotent stem cell (iPSC)-derived RPE cells for patients with age-related macular degeneration (autogenic grafts). However, there are at least two problems with this approach: (1) high cost, and (2) uselessness for acute patients. To resolve these issues, we established RPE cells from induced iPSCs in HLA homozygote donors. In vitro, human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 20 publications
5
95
0
Order By: Relevance
“…The iPS cells are in the preclinical stage, can be generated after inducing the expression of transcription factors associated with pluripotency, and exhibit unlimited self-renewal and differentiation to many cell lineage types. 33 The presented results showed that the most common fiveloci haplotype detected was A*01:01-B*08:01-C*07:01-DRB1*03:01-DQB1*02:01 (3.04%), which had a haplotype frequency of 6.07% per patient in our cohort. [29][30][31] Nevertheless, their high proliferation rate increases the risks associated with products containing iPS (e.g.…”
supporting
confidence: 51%
“…The iPS cells are in the preclinical stage, can be generated after inducing the expression of transcription factors associated with pluripotency, and exhibit unlimited self-renewal and differentiation to many cell lineage types. 33 The presented results showed that the most common fiveloci haplotype detected was A*01:01-B*08:01-C*07:01-DRB1*03:01-DQB1*02:01 (3.04%), which had a haplotype frequency of 6.07% per patient in our cohort. [29][30][31] Nevertheless, their high proliferation rate increases the risks associated with products containing iPS (e.g.…”
supporting
confidence: 51%
“…13,14 For the assay, iPS cell-derived RPE cells were used (TLHD1 or 454E2 lines), while iPS cells (TLHD1 or 454E2 lines) and TLHD1 fibroblasts were prepared for use as controls. Other human RPE lines, such as 59 iPS-RPE (control: 59 iPS cells), were used for the GeneChip analysis.…”
Section: Establishment Of Human Ips Cell-derived Rpe Cellsmentioning
confidence: 99%
“…Detailed information on the RPE-specific medium and signal inhibitors has been described in our previous studies. 13,14 This current research study followed the tenets of the Declaration of Helsinki, and the study was approved by the Institutional Ethics Committee of the Center for Developmental Biology (now Center for Biosystems Dynamics Research), RIKEN.…”
Section: Establishment Of Human Ips Cell-derived Rpe Cellsmentioning
confidence: 99%
“…It had been previously thought that functional human RPEs could be differentiated from either PSCs (Liao et al, 2010;Fields et al, 2016;Sugita et al, 2016) or cultured human fetal RPE cells directly in vitro (Maminishkis et al, 2006;Sonoda et al, 2009) for cell therapy. However, the in vitro differentiation of PSCs into RPEs still needs to be optimized to address safety and effectiveness concern, and human fetal RPE cells are still limiting, due to a lack of donor resources.…”
Section: Rpe Cells Isolated and Characterized From The E60 Chimeric Fmentioning
confidence: 99%